Perimestike As A Value System of Islamic Philosophy In Social Interaction With Indonesian Gayo Society - Syukri Syukri; Sabariah Sabariah (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The entire order of life has experienced social changes and a shift in values, including the traditional speech of the Gayo community, known as "Perimestik" in Islam. The speech is Islamic philosophy's correct, wise, and rational value system. However, it is fading and disappearing due to the influence of technology and globalization. This Perimestike could be used as a philosophy of Islamic life for the Gayo community, referring to Islamic Shari'a. Therefore, this study aimed to examine how Perimestike is a value system of Islamic philosophy in social interaction with the Indonesian Gayo community. Using qualitative, inductive, deductive, and holistic methods, the results showed that Perimestike contains Islamic philosophical, ethical, and moral values or Al-Adab. It is a sacred value system of Islamic philosophy mandated by the tribe’s ancestors to be maintained, realized, and preserved. The system is preserved in line with Islamic teachings according to the customary word “Syariet urum edet lagu zet urum sifet,” meaning “Shari'a and customs are like substances with properties." It is also in line with “Syariet ibarat empus, edet ibarat peger,” meaning “Shari'a is like a garden, the custom is like a fence." However, Perimestike has experienced a shift in values from customary rules and is no longer in harmony according to Islamic philosophy. This is because the Qur'an has the word "qauluzzuur," which means vile (cerak enta sesanah). In “Sumang Peceraken," speaking contrary to Islamic philosophy, customs, Shari'a, and customary manners (jis/jengkat), are prohibited in social interaction with the Gayo Indonesia community.